Faktor-Faktor Penghambat Dalam Implementasi Peraturan Daerah Nomor 10 Tahun 2017 Tentang Pengelolaan Barang Milik Daerah Di Dinas Pekerjaan Umum Dan Penataan Ruang Kota Padang - Septia, Wilda; Yusran, Rahmadani (Jurnal Pemerintahan dan Politik, 2024)
This research aims to identify and analyze the inhibiting factors in the implementation of Regional Regulation Number 10 of 2017 concerning the Management of Regional Property at the Public Works and Spatial Planning Office of Padang City (PUPR). This study was conducted to understand the obstacles that arise in the implementation of this policy, providing an overview of the challenges faced by the agency related to regional asset management. This research uses a descriptive qualitative approach. Data were collected through interviews with stakeholders actively involved in policy implementation, as well as through documentation studies related to the management of regional property at the PUPR Office of Padang City. The results of the study indicate that there are two inhibiting factors in the implementation of the regional regulation. First, the low awareness of users of regional property regarding their responsibility to report the condition and status of the goods they use. This leads to inaccuracies in reporting and recording assets, which impacts asset management. Second, the limited budget allocated to support the implementation of management, especially in asset maintenance. This budget limitation hinders the optimization of regional asset management and poses a challenge for the PUPR Office in effectively implementing the regulation. This research is expected to provide recommendations to improve the implementation of this policy in the future